Application of Very Low Frequency (VLF) Method for Underground River Estimation in Donorojo Sub-District, Pacitan - Ayi Syaeful Bahri; Khusnul Nur Rochmah; M. Haris Miftakhul Fajar; Juan Pandu Gya Nur Rochman; Wien Lestari; Fachri Almawali Abil Fida (Department of Physics, Sebelas Maret University, 2024)
Pacitan is included in the Gunung Sewu karst area in the Southern Mountain Zone, and carbonate rocks dominate the constituent rocks. Karst has a unique drainage system because it is dominated by subsurface flow. This research was conducted in Cemeng and Klepu villages, Donorojo sub-district, Pacitan, with 4 track data. Data were collected using the very low frequency electromagnetic (VLF-EM) method with a track length ranging from 200-450 m, a measurement spacing of 5 m, and a transmitter frequency of 19.8 kHz. Data processing uses filtering and inversion, resulting in a cross-section of resistivity values. Based on the subsurface resistivity cross-section profile, the cavity in the carbonate rock layer with a resistivity value of 0-500 Ωm is identified as an underground river. The underground river is found on tracks 1, 2, 3, and 4 near the surface, with a depth of about 30 m below the surface.